The Effect of Seed Age and Variety Types on the Growth and Production of Tomato (Solanum Lycopersicum L.) Hydroponic Systems - Pamuji Setyo Utomo; Muhamad Abdul Aziz Al Wafa; Nunuk Helilusiatiningsih; Titik Irawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The research aims to determine the effect of seed age and variety types on the growth and production of tomato plants (Solanum lycopersicum L.) with hydroponic systems. This research was conducted with factorial treatment and environmental design Completely Randomized Design (CRD) consisting of 2 factors. Factor I: The age of the seedlings (B) and Factor II. Kinds of varieties (V). The conclusion was that there was an interaction between the age of the seedlings and the variety of varieties in the observation variable for the increase in the number of leaves 28 day in the B2V1 treatment with an average yield of 15.00 leaves.